Psychological Operations and Terrorism: The Digital Domain - Rodger A. Bates; Mara Mooney (Journal of Public and Professional Sociology)
Within the domain of asymmetric warfare, few struggles are won or lost by decisive military battles. Most struggles are decided by a combination of military and political means. Specifically, much of the political leverage is derived from effective psychological operations. The digital domain increasingly has emerged as a major component of this battleground and analysis provides important insights into propaganda and collective behavior in the 21st Century.